Influencia de la fiscalización en la recaudación tributaria de la Municipalidad Distrital de Víctor Larco de Trujillo, año 2016 - Vera Toledo, Palermo Lorenzo (2019)
ABSTRACT The purpose of this research is to determine the influence of taxation on the tax collection of the District Municipality of Víctor Larco Herrera Trujillo 2016. The research problem was to what extent the control policy influences the municipal collection of Victor Larco Herrera Trujillo district 2016. And the hypothesis was the audit allows significantly increase tax collection in the District Municipality of Víctor Larco Herrera Trujillo 2016. The study population consisted of 2,137 taxpayers and the sample of 50 taxpayers. The study method that was used in the research was inductive - deductive, and the survey technique was applied. One of the results obtained in this research was that the Municipal Management in the period 2010 to 2016 show that the level of delinquency from the period 2010 - 2016 has had an auspicious and positive result, despite some ups and downs in 2016 in property tax as in excise taxes. Being the delinquency in property tax the one that more has been reduced from 62.2% (2010) to 24.08% (2016). It was concluded that the implementation of the tax inspection system of the Municipal Entity of the District of Víctor Larco Herrera allowed it to improve the collection of municipal own revenues in a significant manner; resources that have become quality works at the service of all.